Pelatihan Penggunaan Sistem Informasi Whatsapp Blast untuk Meningkatkan Response Rate Tracer Study Pendidikan Vokasi di SMKN 1 Bengkulu - Andang Wijanarko; Aan Erlanshari; Boko Susilo (Abdi Reksa, 2024)
The implementation of the vocational education tracer study at SMKN 1 Bengkulu City carried out by "Bursa Kerja Khusus" (BKK) team experienced many obstacles, so the number of alumni completing the tracer study was still very small. One of the obstacles is that there are no facilities or innovations provided by the school to help the BKK team carry out intense communication with alumni. Therefore, SMKN 1 Bengkulu City really needs an information system to provide information to alumni about how important it is to fill out surveys on the tracer study platform via WhatsApp Blast technology. The method for implementing community service activities is generally carried out through the stages of analysis, design, implementation, as well as training and evaluation. The result of this community service activity is that the website-based WhatsApp Blast information system was successfully built using the PHP, HMTL, CSS Javascript and MySQL programming languages, with the aim of increasing the tracer study response rate at SMKN 1 Bengkulu City. Based on the evaluation of the activities that have been carried out, the BKK team at SMKN 1 Bengkulu City generally believes that the WhatsApp blast system is very helpful in operational tracer study activities. Therefore, it is hoped that the WhatsApp Blast system can increase the number of response rates, or in other words can increase the number of alumni who fill out surveys on the vocational study tracer platform in the nearest period.